Patient safety culture and associated factors among healthcare professional in selected private hospital in Malaysia - Muhammad Mirza Mikhail, Mohd Mahathir (2024)
Patient safety culture is crucial for minimizing avoidable harm in healthcare settings. Despite global advancements, errors and adverse events remain prevalent, particularly in complex environments like hospitals. This study aimed to evaluate the patient safety culture among healthcare professionals in private hospitals and identify influencing factors. Specifically, it sought to determine the level of patient safety culture and explore factors such as age, education, working experience in healthcare, and professional position that may impact it. A cross-sectional study was conducted at a private hospital in Pahang, Malaysia, using the Hospital Survey on Patient Safety Culture (HSOPSC). A sample of 40 healthcare professionals participated, and data was analyzed using descriptive and inferential statistics with SPSS. The overall patient safety culture score was 67.12%, reflecting a moderately positive perception. Strengths were noted in management support (83%) and communication about errors (81.32%), while leadership support (53.33%) and handoffs (50.67%) required improvement. Educational background significantly influenced safety culture, with diploma holders scoring higher than degree holders. Other factors, such as age, working experience in healthcare, and professional position, showed trends but lacked statistical significance. While the overall patient safety culture is positive, there is a need for enhanced leadership involvement and improved communication during transitions of care. Open communication, non-punitive error reporting, and tailored interventions considering educational disparities are essential to further optimizing the safety culture in private healthcare settings.